Same problemy: jak nakreślić ewolucję pojęcia narodu od oświecenia do 1939 roku? - Janowski, Maciej (1963– ) (Instytut Historii PAN, 2019)
p. 281-309
Keywords: political ideas - Poland - history; political ideas - social aspects; signification; concepts - history; nation-building - philosophy; nationalism - history

IPN widziany oczyma Antoniego Dudka - Chojnowski, Andrzej (1945– ) (Wydawnictwo DiG, 2012)
p. 141-152
Reviewed book : Antoni Dudek, Instytut : osobista historia IPN, Warszawa 2011 : Czerwone i Czarne, pp. 367
Keywords: Dudek, Anthony (1966-) - diary; Institute of National Remembrance – Commission for the Prosecution of Crimes against the Polish Nation - history

Sprawa Galicji Wschodniej w Lidze Narodów (1920-1922) - Zaks, Zofia (1935–2001) (Państwowe Wydawnictwo Naukowe, 1967)
p. 127-153
Keywords: League of Nations - history; Galicia, Eastern (Ukraine) - politics and government - 1900-1945; Poland - relations - Ukraine - 1900-1945; Ukraine - relations - Poland - 1900-1945

Jeszcze raz o prezydencie Woodrow Wilsonie - Parafianowicz, Halina (1953– ) (Wydawnictwo DiG, 2002)
p. 205-210
Reviewed book : John Milton Cooper, Breaking the heart of the world : Woodrow Wilson and the fight for the League of Nations, Cambridge 2001, Cambridge University Press, pp. 454
Keywords: Wilson, Woodrow, 1856-1924; League of Nations - history; World War, 1914-1918 - peace; United States - foreign relations - 1913-1921

A Real Brain Twister, or, How to Outline the Evolution of the Concept of Nation between the Enlightenment and the Year 1939? - Janowski, Maciej (1963– ) (Instytut Historii PAN, 2020)
Most historians studying the evolution of the concept of nation and national idea in East Central Europe, assume that through the nineteenth century the political meaning was gradually giving place to the ethnic understanding of ‘nation’. Without radically questioning this evolution of the meaning, I would like to stress that it is far from obvious. Starting with the Enlightenment, the term and concept of ‘nation’ were used so widely in the Polish public debates that it is relatively easy to find quotations to support any generalisation. Any decision about choosing some source materials and discarding some others is inevitably grounded in certain methodological and philosophical assumptions. Some assumptions have to be accepted (for otherwise, a historian would not be able to say anything), but we need to be conscious that their choice is, in the last resort, arbitrary.
p. 5-29
Keywords: conceptual history; concept of nation; political nation; ethnic nation; historical nation; nationality; group identity - Europe, Central - history; group identity - Europe, Eastern - history; ethnicity - Europe, Central - history; ethnicity - Europe, Eastern - history; nation - history